Found Objects in Surrealistic Photography - Shik, Ida A. (Actual Problems of Theory and History of Art, 2018)
The article deals with the issues of the interpretation of the concept of found objects in Surrealist photography. The author identifies such types of found objects in Surrealist photography as found images, ordinary things acquiring the second life and found photographs. The researcher supposes that Surrealist photography creates a specific ‘counter-archive’ of found objects, including items that can describe not only the individual unconscious but also the collective socio-cultural unconscious. The author brings out three main approaches to the treatment of the concept of found object in Surrealist photography: interpretation by the title, using it as a work element or leaving without any comments. The author emphasizes that photographs of found objects are very “democratic”, each thing can become an art object; every person regardless of his or her professional skills can become the creator of found objects or their assemblages. The author concludes that by working with found objects, Surrealist photographers actualize such important concepts as automatism, objective chance, paranoiac-critical method, principle of visual analogy, black humor, principle of paradoxical juxtapositions. The author summarizes that photographs of found objects assure us that surreality is the essential part of the reality hidden in the most banal and habitual things.
Keywords: Surrealism; Surrealist photography; found object; automatism; objective chance; paranoiac-critical method; principle of visual analogy; black humor; principle of paradoxical juxtapositions